(untitled) (Revista Rupturas, 2021)
This article discusses the temporal structure of daily life in two historical neighborhoods in San José City. These neighborhoods are Cristo Rey and Escalante. This paper shows how this structure or architecture behaves like a political time-economy through the time. The logic that organizes daily time in both neighborhood spaces is the social division of labor and the social division of gender. The article also shows that the people who live in Cristo Rey experiment daily routine. And those who live in Escalante neighborhood have flexible time.